Analisis framing pemberitaan korupsi massal di media online detik.com - Ananda, Muhammad Fairuz Satria; Nugraha, Aat Ruchiat; Sumartias, Suwandi (Faculty of Communications Science, Dr. Soetomo University, 2019)
This research aims to determine the construction of PDIP's image from the news framing on them as the party who has the most corrupted fraction members in the event of mass coruption case if the People’s Legislative Council (DPRD) of Malang City by the online media, Detik.com. This research is conducted through constructivism paradigm with the sudty of framing analysis by Robert M. Entman as a conceptual foundation with the framing concept of Entman, namely, define problems, diagnose causes, make moral judgement, and treatment recommendation from journalist side; using the theory of the social mass media as a theoretical foundation. The results of the framing carried out by the online media, Detik.com tend to be neutral in delivering their news on the mass corruption case of the DPRD of Malang City in construction the image of PDIP as the most corrupted party. This is because the media deliver both side cover, even Detik.com’s journalists already included opinions in the titles and selecting images in the news. Although Detik.com tends to be neutral, becase Detik.com just deliver the facts. The bad image construction of PDIP has been constructed already, as the news is considered to be a bad news model.